Decoding algorithms - Lomborg, Stine; Kapsch, Patrick Heiberg (Media, culture & society, 2020)
In this article, we propose to adapt the communication theory concept of ‘decoding’ as a sensitizing device to probe how people come to know and understand algorithms, what they imagine algorithms to do, and their valorization of and responses to algorithmic work in daily media use. We posit the concept of decoding as useful because it highlights a feature that is constitutional in communication: gaps that must be filled by mobilizing our semiotic and socio-cultural knowledge in processes of interpretation before any communication becomes meaningful. If we cannot open the black box itself, we can study the relationships that people experience with algorithms, and by extension how and to what extent these experienced relationships become meaningful and are interwoven with users’ reflections of power, transparency, and justice in digital media. We demonstrate the potential of approaching algorithmic experience as communicative practices of decoding through an exploratory empirical study of how people from different walks of life come to know, feel, evaluate, and do algorithms in daily life. We unpack three prototypical modes of decoding algorithms – along preferred, negotiated, and oppositional modes of engagement with algorithms in daily life.